Spatiotemporal evaluation of water quality, metal pollution, and human health risks in a dredged Urban River, New Jersey, USA - Soetan, Oluwafemi; Zhu, Qingzhi; Feng, Huan (Environmental geochemistry and health, 2025)
Although the short-term effectiveness of remedial sediment dredging (RSD) on mitigating sediment contamination in the lower Passaic river (LPR), New Jersey, USA, was previously established in previous studies, dredging impacts on overlying water and consequential effects on aquatic life and human health were not investigated through model-based risk assessment methods. This study assessed the influence of RSD on metal pollution and toxicological risks upstream and downstream of River Mile-3.4, which was the subject of a 2012 RSD. Over the pre-, during-, and post-dredging periods, threats to aquatic life and humans were greater upstream at River Mile-4 (WQI avg. ≥ 50, PI avg. = 0.9) compared to downstream (River Miles-0 &1), where WQI avg. < 50 and PI avg. = 0.6 & 0.4, respectively. Monte Carlo probabilistic health risk assessment revealed significant probabilities of carcinogenic (≥ 98%) and non-carcinogenic health risks (2–50%) across all study areas and periods, with the highest risks recorded during and shortly after dredging, underscoring the associated toxicant exposure risks to humans from RSD. Significant ( p < 0.05; 0.01) inter-correlations between metals were recorded pre-, during, and post-dredging, with observed negative correlation indicating concentration changes between the dredging and post-dredging periods. Principal component analysis of measured parameters explained two potential categories of pollution sources—(i) in-situ recontamination from dredging residuals and remobilized metals, and (ii) ongoing anthropogenic contributions from combined sewer outfalls and surface runoff. Recent pollution trends in the study areas underscore the effect of seasonality and anthropogenic influences on toxic metal pollution in the LPR and highlight the need for a robust and consolidated protective remedial action comprising engineered and natural measures, policy and engineering control of ongoing pollution sources, and institutional controls to limit human exposure. Graphical abstract